Forecasting international tourism demand in Croatia using Google Trends - Baldigara Tea (Turističko Poslovanje, 2019)
Assuming that the rise of the Internet dramatically changed the modern ways of communication and trends in the tourism sector, as well as the tourist behaviour, the aim of the paper is to quantitatively analyse the influence of the information communication technology development on international tourism demand in Croatia. The purpose of this paper is therefore to demonstrate that Google Trends data can be used as a significant proxy in modelling and forecasting international tourism demand in Croatia. In modelling the number of foreign tourist arrivals a neural network approach was used. The input variable set consisted of nine variables. Beside the traditionally used independent variables, several variables that reflect the ICT and Google Trends influences were included in the model. The research results showed that those variables are strongly correlated in forecasting international tourism demand in Croatia. The empirical results and findings in this paper could certainly contribute to increase the understanding and the knowledge of foreign tourist interest and behaviour and therefore, assure more reliable information to all stake-holders involved in the Croatian tourism sector.